Managing Structural and Dynamic Complexity: A Tale of Two Projects. Issue 4 (August 2014) - Brady, Tim; Davies, Andrew
Previous research suggests complexity may be a significant factor in a project's failure to achieve cost, time, and quality objectives. In this paper, we examine the project complexity literature to develop a simple framework consisting of structural and dynamic complexity. We use this to compare the complexity of two successful construction megaprojects–-Heathrow Terminal 5 and the London 2012 Olympic Park–-to consider how the complexity in the two projects was managed. Our analysis reveals differences in the approach to managing structural and dynamic complexity, but identifies common factors that may help project managers achieve positive outcomes for their complex projects.